Ethics of Leadership Communication in Islam - Muhammad Syarif (QANUN: Journal of Islamic Laws and Studies, 2023)
The formulation of the research problem is how ethical leaders communicate to the public. How effective is the effectiveness of the ethics of communication between leaders and the community in Meunasah Tutong Village, Montasik District, Aceh Besar District. The purpose of this research is to find out the ethics of leaders in communicating with the community and want to know the effectiveness of the ethics of communication between leaders and the community. The methodology used is a qualitative method with a descriptive approach with data collection techniques using observation and interview methods. The number of respondents interviewed was five people consisting of one hamlet head, two members of the community, one tuha peut, the youth leader and the gampong keuchik. The results of the study show that the ethics of leaders communicate with the community in Meunasah Tutong Village, Montasik District, Aceh Besar District. A village built by leaders who lack ethics in communication so that it is clear that changes to the welfare of the community have occurred without having to be assessed from another point of view. Because every human being has a feeling of wanting to be appreciated and wanting to appreciate. When the feeling of wanting to be respected is ignored, the sense of respect cannot be realized so that divisions occur within one community group. Seriousness can be seen based on research results. Not solely because of that, but the way of a good leadership is when the feedback received is in accordance with the expectations desired by a community which is a common goal. the effectiveness of the leader's communication ethics towards the community, namely ineffective communication ethics will have an impact on the social inequality of the community, a sense of togetherness and cooperation will no longer work and this will make a village immoral and dignified.